2018
DOI: 10.1007/s00432-018-2642-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy treatment is associated with altered PD-L1 expression in lung cancer patients

Abstract: This is the first study, in which both PD-L1 and PD-1 expression were analyzed together with the amount of stromal IC infiltration in different histological subtypes of lung cancer before and after platinum-based chemotherapy. Our results confirm that chemotherapy decreases PD-L1 expression of TC in a subset of patients, therefore, rebiopsy and re-evaluation of PD-L1 expression may be necessary for the indication of immune checkpoint inhibitor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 20 publications
3
47
0
2
Order By: Relevance
“…It has already been proven that chemotherapy can change the expression level of PD‐1, but the direction of this change depends on the cell line and chemotherapeutic agent . Moreover, a recent study investigated the expression of PD‐1 and PD‐L1 before and after platinum‐based neoadjuvant chemotherapy in lung cancer patients and found that only PD‐L1 expression decreased significantly after chemotherapy . Conversely, consistent with our study, some studies found opposite results.…”
Section: Discussionsupporting
confidence: 89%
“…It has already been proven that chemotherapy can change the expression level of PD‐1, but the direction of this change depends on the cell line and chemotherapeutic agent . Moreover, a recent study investigated the expression of PD‐1 and PD‐L1 before and after platinum‐based neoadjuvant chemotherapy in lung cancer patients and found that only PD‐L1 expression decreased significantly after chemotherapy . Conversely, consistent with our study, some studies found opposite results.…”
Section: Discussionsupporting
confidence: 89%
“…Similar observations were shown in lung cancer patients, with different histological characteristics and treated with cisplatin or carboplatin-derived chemotherapy [120]. In NSCLC patients treated with paclitaxel/carboplatin/bevacizumab, proliferating peripheral blood CD8 + T cells express a higher level of PD-1 and CTLA-4 compared to non-proliferating CD8 + T cells [110].…”
Section: Platinum Derivatives and Immune Checkpointssupporting
confidence: 78%
“…Interestingly, PD‐L1 expression via the MAPK pathway was reported in cell lines after low‐dose chemotherapy (paclitaxel and cisplatin) (Gong et al, ; Qin, Liu, Zhou, & Wang, ). However, this effect might not translate to the clinical setting, where PD‐L1 levels have been found to decrease, increase or remain unchanged after platinum‐based chemotherapy (Rojkó et al, ). This effect remains of interest, given that drugs such as cisplatin are recommended by the National Comprehensive Cancer Network (NCCN) for cases of unresectable or metastatic HNSCC, and immune checkpoint therapy targeting the PD‐1:PD‐L1 axis is currently approved only after progression following chemotherapy with platinum‐based drugs (Adelstein et al, ).…”
Section: Pd‐l1 In Cancermentioning
confidence: 99%